Falls in the Elderly: A Prospective Study of Risk Factors and Risk Profiles - Graafmans, W. C.; Ooms, M. E.; Hofstee, H. M. A.; Bezemer, P. D.; Bouter, L. M.; Lips, P. (American journal of epidemiology, 1996)
In this prospective study, the authors determined intrinsic risk factors for falls and recurrent falls and constructed a risk profile that indicated the relative contribution of each risk factor and also estimated the probabilities of falls and recurrent falls. In 1992, over a 28-week period, falls were recorded among 354 elderly subjects aged 70 years or over who were living in homes or apartments for the elderly in Amsterdam and the vicinity. During the study period, 251 falls were reported by 126 subjects (36%), and recurrent falls (≥2 falls) were reported by 57 subjects (16%). Associations of falls and recurrent falls with potential risk factors were identified in logistic regression models. Mobility impairment regarding one or more of the tested items (i.e., impairment of balance, leg-extension strength, and gait) was associated with falls (adjusted odds ratio (OR) = 2.6) and was strongly associated with recurrent falls (OR = 5.0). Dizziness upon standing was associated with falls (OR = 2.1) and recurrent falls (OR = 2.1). However, several risk factors were associated with recurrent falls only: history of stroke (OR = 3.4), poor mental state (OR = 2.4), and postural hypotension (OR = 2.0). The authors constructed a risk profile for recurrent falls that included the five risk factors mentioned above. Inclusion of all risk factors in the profile implied an 84% probability of recurrent falls over a period of 28 weeks, compared with 3% when no risk factor was present. The probability of recurrent falls ranged only from 11 % to 29% when predicted by number of falls occurring in the previous year. Physical activity, use of high-risk medication, and the use of vitamin D3, which was randomly allocated to the participants, were not strongly related to either falls or recurrent falls. In conclusion, a large range of probabilities of falls, especially of recurrent falls, was estimated by the risk profiles, in which mobility impairment was the major risk factor. Recurrent fallers may therefore be especially amenable to prevention based on mobilfty improvement. Am J Epidemiol 1996; 143: 1129–36.